Job and worker flows: New stylized facts for Germany - Rüdiger Bachmann; Christian Bayer; Christian Merkl; Stefan Seth; Heiko Stüber; Felix Wellschmied (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2017)
We study the relationship between cyclical job and worker flows at the establishment level using the new German AWFP dataset spanning from 1975-2014. We find that worker turnover moves more procyclical than job turnover. This procyclical worker churn takes place along the entire employment growth distribution of establishments. We show that these procyclical conditional worker flows result almost exclusively from job-tojob transitions. Growing establishments fuel their employment growth by poaching workers from other establishments as the boom matures. At the same time, non-growing establishments replace these workers by hiring from other establishments and non-employment.
Keywords: E32; J23; J63; 330; job flows; worker flows; aggregate fluctuations